Youth orientation in AR4D: Possible dimensions - Thorsen, Dorte; Glover, Dominic; Cabral, Lidia (Institute of Development Studies, 2023)
Youth is recognized as a key demographic in international agricultural and rural development. Young men and women hold large stakes in the future of sustainable agri-food systems, and they are recognized as an important target group for agricultural research for development (AR4D) interventions. This paper was commissioned by the CGIAR GENDER Impact Platform with the aim of pushing the way we think about engaging with youth, who youth are, and how the diversity among youth can be reflected in AR4D to advance gender equality and inclusivity. In this presentation, we focus on conceptual approaches towards youth. Like any other generation, youth are diverse and differentiated, but the heterogeneity in young people’s situations, capacities and experiences is sometimes ignored. Representations of youth frequently define youth as a simple, distinct and homogeneous demographic category, defined chiefly by age and often as genderneutral personae or simple binary categorizations of male and female youth. Drawing on recent scholarly debates, we explore what insights can be gained from three alternative perspectives on youth: youth as a transitional phase of life; youth in a generational perspective; and youth as an identity and cultural resource for action. We argue that these perspectives constitute the building blocks of a relational conceptual framework that can guide youth-sensitive research and program design. We contend that it is vital to understand youth as a relational concept and status, in contrast to static and dogmatic framings, which mistakenly characterize youth as a mere age category or a standardized, universal experience.